Is science multicultural? : postcolonialisms, feminisms, and epistemologies - Harding, Sandra G. (Race, gender, and science., 1998)
"Sandra Harding explores what practitioners of European/American, feminist, and postcolonial science and technology studies can learn from each other. She discusses the array of postcolonial science studies that have flourished over the last three decades and probes their implications for "northern" science."--Jacket